A full structural mechanical description of beam elements for rotors in electrical machines. Issue 5 (7th September 2015) - Oszkár Bíró, Professor David A. Lowther and Dr Piergiorgio Alotto, Professor; Poganski, Joshua; Mair, Mathias; Ellermann, Katrin
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to get a more consistent finite element description for three-dimensional (3D) Timoshenko beam elements. It extends the common description of beam elements by modifying the shape functions and considers the warping of the cross-section due to torsion. Design/methodology/approach – The paper builds mainly on a finite element description of 3D Timoshenko beam elements. The implementation of high-order shape functions for torsion is done by adding a seventh degree of freedom to the system. Findings – The results reveal that for some beams, depending on their physical dimensions, the warping of the cross-section has large influence. In comparison to a conventional FE program, the extended finite element description considers the warping and yields more accurate results. Practical implications – An application of the extended finite element description is done with an implementation of the code in MATLAB. The static and dynamic behavior of a rotor in an electrical machine is investigated. Originality/value – This paper presents a more consistent finite element description of 3D Timoshenko beam elements considering the warping. A comparison to conventional finite element descriptions is given.